Analysis of processes self-organizations in the conditions of boundary friction - Гедзюк, Т.В. (Problems of Tribology, 2014)
The modern state of theory of molecular structure of boundary lubricating layer and the problems of self-organizations of the systems which work in the conditions of boundary friction is analysed.